O paradigma racionalista e sua repercussão no direito processual brasileiro. - Pereira, Mateus Costa (2010)
The dissertation exams the rational paradigm and the modern science paradigm, in a historic overview that redeems its initial draft, in the historical line and observes, critically, its influence in Law, specially, in Brazilian procedure laws. The approach take on this subject was divided in two different parts, differ by its utilized methods, at first the historic-hermeneutic and secondly critic-hermeneutic. The paper exams the creation of a modern paradigm, originally understood upon the analysis of epistemological assumptions that forms it, demonstrating that they were developed in the so called natural science and afterwards became parts of foundations of a legal system. The systematization originally from Biology, as scientific rule, propagates to the fellow knowledgeable paths, as a necessary pathway to all status of science.